Integrating websites to self access language learning: a strategic way to facilitate the autonomous learning - S Supardi (University of Muhammadiyah Purwokerto, 2019)
Up to this present time, self access language learning (SALL) has become an interesting topic for study. Many scholars have devoted their attention to the study on this topic that many of their papers are published in Studies in Self Access Learning journal. Though many studies have discussed this topic, the websites that can be integrated into SALL as a strategic way to ficilitate the autonomous learning remains underresearched. This paper is based on a research looking at the integration of websites into SALL from the perspective of SALL materials in an online SALL centre. It looks at which English language skills are offered as SALL materials and which websites provide SALL materials. The data concerning these two themes were collected from the online visit to to Self Access Centre and INdependent Learning (SACIL) set up at the University of Waikato. SALL materials in SACIL include general language skills, grammar, reading, listening, speaking and pronunciation, writing, punctuation, vocabulary and spelling, IELTS, and study skills and exam preparation which are linked to a large number of websites. With these website-based SALL materials, the learners over the world can finally practice their skill autonomously.Key words: website, self access laguage learning, autonomous learning.